Copy number variations in DCC/18q and ERBB2/17q are associated with disease‐free survival in microsatellite stable colon cancer. Issue 7 (1st April 2017) - Sefrioui, David; Vermeulin, Thomas; Blanchard, France; Chapusot, Caroline; Beaussire, Ludivine; Armengol‐Debeir, Laura; Sesboué, Richard; Gangloff, Alice; Hebbar, Mohamed; Copin, Marie‐Christine; Houivet, Estelle; Schwarz, Lilian; et al.
Abstract : We conducted a prospective study to assess the prognostic impact of selected copy number variations (CNVs) in Stage II–III microsatellite stable (MSS) colon cancer. A total of 401 patients were included from 01/2004 to 01/2009. The CNVs in 8 selected target genes, DCC/ 18q, EGFR/ 7p, TP53/ 17p, BLK /8p, MYC /8q, APC /5q, ERBB2 /17q and STK6 /20q, were detected using a quantitative multiplex polymerase chain reaction of short fluorescent fragment (QMPSF) method. The primary end‐point was the impact of the CNVs on the 4‐year disease‐free survival (DFS). The recurrence rate at 4 years was 20.9%, corresponding to 14% Stage II patients versus 31% Stage III patients ( p  < 0.0001). The 4‐year DFS was significantly decreased in patients with a loss at DCC /18q ( p  = 0.012) and a gain at ERBB2 /17q ( p  = 0.041). The multivariate analysis demonstrated that Stage III, a loss at DCC /18q and a gain at ERBB2 /17q were independent factors associated with DFS. A combination of DCC /18q and ERBB2 /17q was also associated with relapse, with the hazard ratio increasing from 1 to 2.4 (95% confidence interval (CI), 1.5–4.1) and 3.1 (95% CI, 1.2–8.4) in the presence of 0, 1 or 2 alterations, respectively ( p  = 0.0013). CNVs in DCC /18q and ERBB2 /17q are significantly associated with DFS in Stage II–III MSS colon cancer. Abstract : What's new? Small chromosomal changes can have a big impact on cancer survival. In this article, researchers analyzed how colon cancer prognosis was affected by a gain or loss of repeats in microsatellite sequences affected. They collected data on copy number variation at 8 loci from 400 patients with Stage II–III tumors. Two loci stood out: a loss at DCC/18q and a gain at ERBB2/17q both associated with higher risk of relapse, either individually or in combination. Identifying these variants could help with weighing treatment options for localized colon cancer.